Standardisasi Tata Cara Pengurusan Jenazah Berdasarkan Perspektif Hukum Islam dalam Meningkatkan Kualitas Ibadah Masyarakat - Rahmi, Muarifah; Samsuddin, Samsuddin; Hamzah, Ekawati; Asrianti, Asrianti; Khasanah, Uswatun; Nurfadillah, Nurfadillah; Yasmin, Putri Aulia; Husna, Asmaul; Ikhsan, MUhammad; Ferdiyansa, Muh.; Syam, Muhammad Afiq Rijal (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
Managing a corpse is a collective obligation (fardu kifayah) for Muslims. However, in many communities, understanding of the procedures for handling a corpse in accordance with Islamic law is often limited or dominated by local traditions that do not necessarily align with Islamic legal standards. The limited number of competent practitioners (amirs) also hinders maintaining the quality of this worship. This Community Service (PKM) activity aims to provide education and standardize procedures for handling a corpse from an Islamic legal perspective to improve the understanding and quality of worship in carrying out religious obligations in Uloe, Dua Boccoe District, Bone Regency. The activity used the Participatory Action Research (PAR) method through three main stages: (1) Dissemination of theory regarding the laws of handling a corpse, (2) Technical training (workshop) covering practical aspects of washing, shrouding, praying, and burying the body, and (3) Mentoring and evaluation through independent simulations by participants. The results of the activity showed significant improvements in the cognitive and psychomotor aspects of the participants. The community now has a standardized reference that minimizes doubts in practice in the field. Furthermore, the formation of skilled community groups is expected to ensure the continuity of corpse management in accordance with the Sunnah (traditional Islamic law) in local communities. Standardizing corpse management procedures effectively increases community confidence and the quality of worship. Ongoing education is necessary to ensure Islamic legal literacy regarding corpse management is maintained from generation to generation.